A trajetória do ambiente jurídico-institucional do setor de software no Brasil e na Índia: identidades, diferenças e repercussões - Ferraz, Joana Varon (2010)
For over 30 years, Brazil has developed specific policies to foster computer industry. Goals and institutional frameworks have been outlined for the sector, since the National Informatics Policy of the 70’s, going through the Market Reserve Period of the 80’s, until nowadays, when Informatics Communication Technologies (ICT) are seen as prioritary area for Industrial Policy. Among the current goals, we can highlight the focus on increasing exports of software products and services. However, despite these claims, the country exports on the field haven’t been particularly expressive at the global market. On the other hand, India, which, just as Brazil, is also considered an emerging economy portrayed on the list of BRIC, was responsible for exporting about USD$47 billion in software and IT services by 2009, emerging as a global player for the sector. The implementation of a sophisticated activity such as software industry in a developing country like India definitely calls our attention. Certainly, legal-institutional arrangements were implemented at that country. Which? To what extent such arrangements helped the development of Indian industry? What about Brazil? This paper assumes that the legal-institutional framework developed at the countries have established different knowledge flows, leading to different development paths for each software industry. The generic goal of this research is to investigate how, among other socio-economic factors, these legal-institutional arrangements have outlined different knowledge flows. For the matter, legal-institutional framework is considered as all regulation that establishes institutions, policies and conditions to a particular subject. This paper also assumes that the software industry is based on knowledge-intensive activities. Therefore, the analysis will focus on legal-institutional arrangements that had and/or still have influence over knowledge flows directly related to software industry, thus, trade policies (export and import, property rights, etc) and investment policies for innovation developed in India and Brazil to foster the sector. The goal is not to take India as the ideal model to be followed by Brazil, or even to exhaust the question of what would be an ideal public policy for this sector, which would mean going beyond a legal-institutional analysis. The key question to be faced is not if the State has a developmental role, but what are the different types of State involvement that can be observed and what are its effects. To reach these goals, in addition to literature reviews, a fieldwork was developed at India (Delhi, Mumbai, Bangalore) and Brazil (São Paulo, Brasilia and Rio de Janeiro), where interviews were conducted with enterprises and software associations, policy makers and academics who study the industry.